THE INFLUENCE OF THE AUDITORY INTELLECTUALLY REPETITION (AIR) LEARNING MODEL ON LEARNING OUTCOMES IN AL-QUR'AN HADITH SUBJECT CLASS XI STUDENTS OF MADRASAH ALIYAH TASSBEH BAITUL QUR'AN PINRANG REGENCY (International Conference on Social and Islamic Studies, 2022)
This study discusses the influence of the Auditory Intellectually Repetition (AIR) learning model on Learning Outcomes of the Qur'an Hadith. This research was conducted with the aim of; 1) Knowing the results of learning the Qur'an Hadith of students who are taught without using the Auditory Intellectually Repetition (AIR) learning model in class XI Madrasah Aliyah Tassbeh Baitul Qur'an, Pinrang Regency. 2) Knowing the learning outcomes of Al-Quran Hadith students who are taught using the Auditory Intellectually Repetition (AIR) learning model in class XI Madrasah Aliyah Tassbeh Baitul Qur'an, Pinrang Regency. 3) Knowing whether the application of the Auditory Intellectually Repetition (AIR) learning model affects the learning outcomes of the Al-Qur'an Hadith class XI students of Madrasah Aliyah Tassbeh Baitul Qur'an Pinrang Regency. Basically this research is a quasi-experimental research that has a control group, with a quantitative research approach that utilizes variables as research objects and each variable must be defined in the form of an operational variable. The sample and population in this study were all class XI MA Tassbeh Baitul Qur'an, namely class XI Religion 1 as the experimental class and XI Religion 2 as the control class. The sampling technique is purposive sampling or sampling technique with certain considerations, using observation sheets and tests of learning outcomes for Al-Qur'an Hadith subjects as research instruments. Data processing to obtain research results using descriptive and inferential statistical data analysis. The results of this study indicate that: 1) The maximum scores obtained in the pre-test control class were 92 and the post-test were 96, while the minimum was 32 for the pre-test and 60 for the post-test, and the mean pre-test was 64.44 and post-test 73.11 with a standard deviation in the pre-test was 15.38 and the post-test was 9.35. 2) The experimental class got the maximum score on the pre-test, namely 92 and the post-test, 96, the minimum pre-test score was 48 and the post-test, 68, the mean pre-test for the experimental class was 67.57 and the post-test was 79.35 , while the standard deviation obtained by the pre-test was 12.17 and the post-test was 7.97. 3) Researchers have proven that the Auditory Intellectually Repetition (AIR) learning model has an influence on student learning outcomes in the Al-Qur'an Hadith subject at Madrasah Aliyah Tassbeh Baitul Qur'an Pinrang Regency, thus the research hypothesis H1 is accepted. The implications of this research are as study material for improving the quality of the learning process in the classroom with the aim of increasing student learning outcomes, through these improvements educators have more meaningful achievements and further process evaluation materials, and students can improve their quality through competency achievement. obtained during the learning process